Is the population properly informed about sleep disorders? A população está devidamente informada sobre os distúrbios do sono? - Eleida Pereira Camargo; Luciane Bizari Coin Carvalho; Lucila Bizari Fernandes Prado; Gilmar Fernandes Prado (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To measure the prior knowledge about sleep disorders and patient's ability to report their problems adequately to health professionals. METHODS: We analyzed 208 patient's records and extracted the following information: date of birth, gender, medical diagnostic hypotheses, patient's primary complaint in their words, considering the most appropriated semantic approximation to the perceptual phenomena, either by their own or by reasoning information from the partner. We compared the agreement (Kappa's test) between patient's complaint and medical diagnosis. The 95% confidence interval was used to analyze proportions. RESULTS: We found strong correlations for bruxism; moderate for snoring, insomnia, nightmares, somniloquy, and restless legs syndrome; fair for excessive movement during sleep (EMDS) and obstructive sleep apnea syndrome (OSA). CONCLUSIONS: The observed correlations were heterogeneous, but important diseases such as OSA and EMDS in children showed fair and weak correlations. This suggests an unsatisfactory knowledge level among the population about these disorders, despite their high prevalence and impact on patient's overall health. OBJETIVO: Avaliar o conhecimento da população investigada sobre os distúrbios do sono e sua capacidade de reportá-los adequadamente aos profissionais de saúde. MÉTODOS: Foram analisados ​​208 prontuários de pacientes, dos quais foram extraídos os seguintes dados: data de nascimento, sexo, hipótese diagnóstica médica e queixa principal do paciente. Foram comparadas as queixas e as hipóteses diagnósticas, considerando-se o intervalo de confiança de 95% para as proporções entre estas variáveis, determinando-se sua concordância por meio do teste Kappa. RESULTADOS: Foram encontradas concordâncias acentuadas em relação ao bruxismo; moderadas para ronco, insônia, pesadelos, sonilóquio e síndrome das pernas inquietas; concordância regular para movimentação excessiva durante o sono (EMDS) e síndrome da apneia obstrutiva do sono (SAOS). CONCLUSÕES: As concordâncias observadas foram heterogêneas, mas doenças importantes, como SAOS e EMDS, apresentaram correlações regulares e ausentes na amostra infantil, sugerindo insatisfatório nível de conhecimento da população sobre estes distúrbios, apesar da alta prevalência e do impacto sobre a saúde do paciente.